Kualitas Hidup Perawat di Ruang Isolasi Covid-19 Rumah Sakit X Banyumas - Win Asmo Dewanti; Wahyu Ekowati; Wahyudi Mulyaningrat (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Caring for Covid-19 patients for long periods can lead to fatigue. This condition can have an impact on the quality of life of nurses. The quality of life includes several aspects, namely aspects of physical health, psychological, and social relationships, and relationships with the environment. This study uses a non-analytic descriptive research method with an observational approach. The sample used in the study was 60 nurses in the Covid-19 isolation room at the Banyumas Hospital. The sampling technique in this study used a total sampling technique. Measurement of the quality of life of nurses using the WHOQOL-BREF instrument. The results of the study based on each domain stated that 60% of respondents were in the category of good physical health, 55% of respondents were in the category of good psychological health, 48.3% of respondents were in the category of very good social relations, and 46.7% respondents are in the category of good environmental relations. It can be concluded that the quality of life of nurses in the Covid-19 isolation room at the X Hospital includes aspects of physical health, psychological health, social relations, and relationships with the environment.